Estimating the polygamma functions for negative integers - Salem, Ahmed; Kilicman, Adem (SpringerOpen, 2013)
The polygamma functions ψ(r)(x) are defined for all x>0 and r∈N. In this paper, the concepts of neutrix and neutrix limit are applied to generalize and redefine the polygamma functions ψ(r)(x) for all x∈R and r∈N. Also, further results are given.